Penggunaan GeoGebra sebagai Program Komputer Matematika dalam Meningkatkan Motivasi Belajar Siswa - Amelia Pujianti (Papanda Publisher, 2025)
This study aims to analyze the use of GeoGebra as a mathematical computer program in enhancing students' learning motivation through the Systematic Literature Review (SLR) method. Learning motivation is a crucial factor in the success of mathematics learning, yet many students still experience difficulties and lose interest in this subject. A total of 15 scientific articles published between 2017-2025 were analyzed with inclusion criteria covering research focusing on the use of GeoGebra and its impact on student learning motivation. The review results show that GeoGebra has a positive impact on student learning motivation across various mathematical materials such as geometry, algebra, quadratic functions, and geometric transformations. The dynamic and interactive visualization provided by GeoGebra helps students understand abstract concepts more concretely. Research shows a significant increase in student learning motivation with an average increase ranging from 6.5% to 86.8%. GeoGebra can be an effective alternative learning media to enhance student learning motivation.